(3JbQjQ GdbhGfjf GdeJOGhdI ef Yde GdefGXQIs - (3GdeQYTj, SGLbdj RGOg, eMeO Hf CHi HcQ, J(B1145(3g`s
(3ChdgG (B:s
(3HSe Gddg hHMeOg gPG JbQjQ cJHJg JNdUG Yf GbJQGM HYV GdWdHI hdjchf dge ebOeI dWdH aQhYgG GdfGOQI , hYde GdefGXQI bhGfjf jYQa HgG CMhGd GdCHMGK GdLRFjIs
(3BNQgG (B:s
(3Ke GYde GdebOeI GdhGMOI ef GdbjGS GdMedj aGYde Cf GdbjGS eQcH cbhdfG aj EKHGJ GdYGde Cf GdYGnde dg eDKQ dCf cd eJZjQ MGOK heYQaI GdeWhjGJ JMJGL Edi HSW hdjcf gPG BNQ GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\60s
(3EjVGM Gdecfhf (B1/315s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs